Kajian learning obstacle materi persamaan dan pertidaksamaan linear satu variabel pada pembelajaran matematika di sekolah menengah pertama - Lelis Sulastri; Ebih Abdul Rachim Arhasy (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
The purpose of this research is to identifying of learning obstacle in equalities and inqualities linear one variable. This research uses qualitative method. The data collection was a test that uses to identifying learning obstacle. The instrumental of this research is the reseacrher and test instrumental. The data source of this research are students were learned materials of equalities and inqualities one variable, they are students at the second grade, third grade of SMP IT Nurul Jannah and the students at the first grade of SMA Negeri 1 Ciawi. The data were analyzed by students response about instrumental is given, categorised students response into some categorys, analyzed causality of learning obstacle, and connected causality of learning obstacle with theoretical of learning to arrange initial of DDR. The result of this study was discovery five types of learning obstacle is learning obstacle type 1 (learning obstacle related concepts in materials equalities and inqualities linear one variable), learning obstacle type 2 (learning obstacle related prosedural to finished problem of equalities and inqualities linear one variable), learning obstacle type 3 (learning obstacle related problem solving materials equalities and inqualities linear one variable), learning obstacle type 4 (learning obstacle related connction equalities and inqualities linear one variable with other concept in mathematics). The result of repersonalization concept in equalities and inqualities linear variable.Keywords: Learning obstacle, repersonalization materials.